Detection of Toxoplasma gondii in the reproductive system of male goats - Santana,Luís Fernando (2010)
Male goats of mating age serologically negative for Toxoplasma gondii were divided into three groups: GI - controls (placebo) (n = 2); GII - infected with 1 × 10(6) tachyzoites (RH strains) (n = 2); and GIII - infected with 2 × 10(5) oocysts (P strains) (n = 2). Clinical, hematology, parasite and serology tests and studies of parasites in the semen through bioassay and polymerase chain reaction (PCR), and in reproductive organs (bioassay) were performed to assess toxoplasma infection. Serological titers peaked at 4096 in two animal groups infected with the protozoan. The bioassays allowed an early detection of protozoa in semen samples of tachyzoite-inoculated animals. T. gondii DNA was identified through PCR in the semen in five (Days 5, 7, 28, 49, and 70) and two (both at day 56) different days post-inoculation in GII and GIII animals, respectively. It was also possible to detect T. gondii DNA in reproductive organs (prostate pool, testicles, seminal vesicle and epididymis) of goats inoculated with either tachyzoites or oocysts. The present study suggests the possibility of venereal transmission of T. gondii among goats and it should be further assessed.